Iron(II) acetylacetonate containing brightener and sulphur containing carrier in nickel plating - Gezerman, A. O.; Corbacioglu, B. D. (MANEY PUBLISHING, 2013)
The effects of an iron(II) acetylacetonate containing brightening agent and a carrier on colour and mechanical properties of nickel plating were investigated to determine optimal electroplating process parameters. The brightening agent contained metasulphobenzaldehyde, pyridine-3sulphonic acid, p-vinylbenzenesulfonic acid, o-benzoylsulphonamide, sodium saccharine and iron(II) acetylacetonate. The carrier comprised sodium saccharine and sodium allyl sulphonate in water. Plating colour was analysed by visible region spectrophotometry at 350 nm under 6500 K illumination (CIE Standard Illuminant D65). Electron microscopy confirmed that carrier facilitated nickel deposition onto the surface and increased cohesion, thus allowing complete coverage. Moreover, brightening agent increased the bath pH, while carrier did not. In bending experiments on a coated plate, brightening agent increased hydrogen embrittlement, although desired decorative appearance was obtained. Finally, the optimum concentrations of carrier and brightening agent were found to be 12 and 0.4 g L-1 respectively.
Keywords: Brightener; Carrier; Acetylacetonate; Embrittlement; Spectrophotometry; NI-P COATINGS; CORROSION-RESISTANCE; ELECTRODEPOSITION; DEPOSITION; ALLOY; ELECTROLYTES; MORPHOLOGY; Materials Science